Penanganan Pascapanen Untuk Peningkatan Mutu Dan Daya Saing Komoditas Kakao - S. Joni Munarso (Badan Penelitian dan Pengembangan Pertanian, 2016)
ABSTRACTDetermination of cocoa production growth rate of 3.9% per year must be complemented by increasing competitiveness of cocoa in order to assure that cocoa production could provide added value and prosperity for farmers. The weakness of Indonesian cocoa in market competition mainly occurs due to the low quality of cocoa beans, caused by high levels of nonfermented beans (>3%) and impurity content (>2%). Meanwhile, the market also implemented food safety requirements as well as taste preferences that need to be anticipated by implementing fermentation process. Technology for fermentation of cocoa beans has already been available, but innovation on policy still seems to need improvement. Fermentation institution needs to be built, including through revitalization of processing unit by making it as business entities, which are well managed to obtain economical, social and environmental benefit optimally. Farmers and traders also need to implement good agricultural and good handling practices. Therefore, guidance of implementation and intensive assistanceneed to be prepared. Consequently, agricultural activities are needed to be revitalized.Keywords: Cocoa, postharvest handling, quality, competitivenessabstrakPenetapan laju pertumbuhan produksi kakao sebesar 3,9% per tahun harus diimbangi dengan peningkatan daya saing agar produksi kakao mampu memberikan nilai tambah dan kesejahteraan bagi petani. Kelemahan kakao Indonesia dalam persaingan di pasar global terutama adalah mutu biji rendah karena tingginya kadar biji tidak difermentasi (> 3%) serta kadar kotoran (> 2%). Selain itu, pasar juga menerapkan persyaratan keamanan pangan yang ketat dan preferensi cita rasa konsumen yang perlu diantisipasi antara lain dengan menerapkan proses fermentasi. Inovasi teknologi fermentasi biji kakao telah tersedia, namun inovasi kebijakan masih perlu penyempurnaan. Kelembagaan fermentasi perlu dibangun, di antaranya melalui revitalisasi unit pengolahan hasil (UPH) dengan menjadikan UPH sebagai unit bisnis yang dikelola secara terorganisir untuk mendapat manfaat ekonomis, sosial, dan lingkungan secara optimal. Penerapan kaidah praktik pertanian dan penanganan yang baik juga perlu dilakukan oleh petani maupun pedagang pengumpul. Untuk itu panduan pelaksanaan dan pendampingan secara intensif perlu disiapkan. Penerapan praktik pertanian dan pengolahan yang baik perlu didukung dengan revitalisasi penyuluhan.